2011
DOI: 10.1091/mbc.e11-05-0411
|View full text |Cite
|
Sign up to set email alerts
|

A contractile actomyosin network linked to adherens junctions by Canoe/afadin helps drive convergent extension

Abstract: Coordination of adhesion and the actin cytoskeleton is critical in morphogenesis. Drosophila germband extension is a model for convergent extension. Canoe/afadin is found to have a novel role in this process. It helps to coordinate a contractile apical actomyosin network with cell shape change and regulates apical polarity protein localization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

26
241
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 161 publications
(269 citation statements)
references
References 39 publications
26
241
2
Order By: Relevance
“…Recent work has demonstrated that this separate, apically localized pool of pulsating myosin-II is connected to AJs. Whereas this apical myosin-II clearly contributes to body elongation, it seems dispensable for rosette formation; in mutants in which apical myosin-II is specifically disrupted, rosettes still form, although apical myosin-II forms rings around vertices instead of its usual tight localization around rosette centers (Sawyer et al, 2011). Thus, myosin-II-dependent rosette formation and resolution is just one of at least two myosin-dependent mechanisms that lead to epithelial tissue elongation.…”
Section: Drosophila Epithelial Morphogenesismentioning
confidence: 99%
“…Recent work has demonstrated that this separate, apically localized pool of pulsating myosin-II is connected to AJs. Whereas this apical myosin-II clearly contributes to body elongation, it seems dispensable for rosette formation; in mutants in which apical myosin-II is specifically disrupted, rosettes still form, although apical myosin-II forms rings around vertices instead of its usual tight localization around rosette centers (Sawyer et al, 2011). Thus, myosin-II-dependent rosette formation and resolution is just one of at least two myosin-dependent mechanisms that lead to epithelial tissue elongation.…”
Section: Drosophila Epithelial Morphogenesismentioning
confidence: 99%
“…Considering that (i) drebrin may influence myosin activity (Ishikawa et al, 2007;Kubota et al, 2010) and (ii) actomyosin contractility can be involved in the regulation of cell-cell contacts (Sawyer et al, 2011;Taguchi et al, 2011), we explored the potential role of the actomyosin system in drebrin-dependent regulation of cell junctions, using myosin II-inhibiting drugs such as Y-27632 (inhibiting ROCK) and blebbistatin (not shown). However, using a wide variety of conditions, we did not detect a significant influence on drebrin-dependent stability of nectin at junctions.…”
Section: (D-o) Confocal Images Of Huvec Expressing Mito-drebrin-pp-gfmentioning
confidence: 99%
“…(C) Shear stress that is generated by the flow of body fluid acts on surfaces of tubular tissues formed by endothelial or epithelial layers, as experienced by endothelial cells in blood vessels (Vermot et al, 2009). (D) Hydrostatic pressure exerted by a non-compressible internal tissue on a shrinking outer epithelial tubule, as observed during C. elegans embryonic elongation (Ciarletta et al, 2009 junction shrinkage during Drosophila germband cell intercalation (Fernandez-Gonzalez and Zallen, 2011;Rauzi et al, 2010;Sawyer et al, 2011). In contrast to cells without overt tissue planar polarity (fly mesoderm and amnioserosa), germband cells are polarized.…”
Section: Generation Of Intrinsic Forces Within Cellsmentioning
confidence: 99%
“…Here, myosin II foci preferentially move towards junctions with less E-cadherin (Rauzi et al, 2010). This pulse is regulated by a-Catenin and Canoe, which promote interactions between actomyosin and adherens junctions (Rauzi et al, 2010;Sawyer et al, 2011). The primary cause for the pulsatile nature of actomyosin foci probably reflects the dynamic instability that was observed for ensembles of motor proteins under load (Jülicher and Prost, 1995;Kruse and Riveline, 2011).…”
Section: Generation Of Intrinsic Forces Within Cellsmentioning
confidence: 99%